Impact on creative thinking by an intrinsic calm approach of interior architecture students / Dahlia Mohd Shariff - Mohd Shariff, Dahlia (Institute of Graduate Studies, UiTM, 2012)
Creativity, generation of ideas and artistic ability for visual communication are highly essential to an interior architect. Interior Architecture/Design educators and creativity theorists differ in their perspectives towards the activity of generating ideas, how ideas arise in the mind, the “Eureka” or “Ah-ha” experience, the point of illumination. To the creativity practitioners, calmness helps to improve creativity, to the Interior Architecture/Design educators this is not so. The education and training of the interior architects are still very orthodox and places high emphasis of achievement and performance through stressful measures of overload of work and time datelines. This research studied the effects of being calm onto the creative thinking and artistic performance, intrinsically, within a person, and not from the external. The first insight, incubation and illumination stages of the creative process are very intuitive and not easily explained unlike the preparation and verification stages